Cytoskeletons in the Closet—Subversion in Alphaherpesvirus Infections - Christopher E. Denes; Monica Miranda-Saksena; Anthony L. Cunningham; Russell J. Diefenbach (Viruses, 2018)
Actin filaments, microtubules and intermediate filaments form the cytoskeleton of vertebrate cells. Involved in maintaining cell integrity and structure, facilitating cargo and vesicle transport, remodelling surface structures and motility, the cytoskeleton is necessary for the successful life of a cell. Because of the broad range of functions these filaments are involved in, they are common targets for viral pathogens, including the alphaherpesviruses. Human-tropic alphaherpesviruses are prevalent pathogens carried by more than half of the world’s population; comprising herpes simplex virus (types 1 and 2) and varicella-zoster virus, these viruses are characterised by their ability to establish latency in sensory neurons. This review will discuss the known mechanisms involved in subversion of and transport via the cytoskeleton during alphaherpesvirus infections, focusing on protein-protein interactions and pathways that have recently been identified. Studies on related alphaherpesviruses whose primary host is not human, along with comparisons to more distantly related beta and gammaherpesviruses, are also presented in this review. The need to decipher as-yet-unknown mechanisms exploited by viruses to hijack cytoskeletal components—to reveal the hidden cytoskeletons in the closet—will also be addressed.